Psychosocial working conditions in a representative sample of working Australians 2001–2008: an analysis of changes in inequalities over time. Issue 9 (30th May 2013) - LaMontagne, A D; Krnjacki, L; Kavanagh, A M; Bentley, R
Abstract : Background: A number of widely prevalent job stressors have been identified as modifiable risk factors for common mental and physical illnesses such as depression and cardiovascular disease, yet there has been relatively little study of population trends in exposure to job stressors over time. The aims of this paper were to assess: (1) overall time trends in job control and security and (2) whether disparities by sex, age, skill level and employment arrangement were changing over time in the Australian working population. Methods: Job control and security were measured in eight annual waves (2000–2008) from the Australian nationally-representative Household Income and Labour Dynamics of Australia panel survey (n=13 188 unique individuals for control and n=13 182 for security). Observed and model-predicted time trends were generated. Models were generated using population-averaged longitudinal linear regression, with year fitted categorically. Changes in disparities over time by sex, age group, skill level and employment arrangement were tested as interactions between each of these stratifying variables and time. Results: While significant disparities persisted for disadvantaged compared with advantaged groups, results suggested that inequalities in job control narrowed among young workers compared with older groups and for casual, fixed-term and self-employed compared with permanent workers. A slight narrowing of disparities over time in job security was noted for gender, age, employment arrangement and occupational skill level. Conclusions: Despite the favourable findings of small reductions in disparities in job control and security, significant cross-sectional disparities persist. Policy and practice intervention to improve psychosocial working conditions for disadvantaged groups could reduce these persisting disparities and associated illness burdens.